Facilitating Dental Student Reflections: Using Mentor Groups to Discuss Clinical Experiences and Personal Development. Issue 10 (1st October 2016) - Koole, Sebastiaan; Christiaens, Veronique; Cosyn, Jan; De Bruyn, Hugo
Abstract : Despite the consensus on the importance of reflection for dental professionals, a lack of understanding remains about how students and clinicians should develop their ability to reflect. The aim of this study was to investigate dental students' and mentors' perceptions of mentor groups as an instructional method to facilitate students' reflection in terms of the strategy's learning potential, role of the mentor, group dynamics, and feasibility. At Ghent University in Belgium, third‐ and fourth‐year dental students were encouraged to reflect on their clinical experiences and personal development in three reflective mentor sessions. No preparation or reports afterwards were required; students needed only to participate in the sessions. Sessions were guided by trained mentors to establish a safe environment, frame clinical discussions, and stimulate reflection. Students' and mentors' perceptions of the experience were assessed with a 17‐statement questionnaire with response options on a five‐point Likert scale (1=totally disagree to 5=totally agree). A total of 50 students and eight mentors completed the questionnaire (response rates 81% and 89%, respectively). Both students and mentors had neutral to positive perceptions concerning the learning potential, role of the mentor, group dynamics, and feasibility. The mean ideal total time for sessions in a year was 99 minutes (third‐year students), 111 minutes (fourth‐year students), and 147 minutes (mentors). Reported reflective topics related to patient management, frustrations, and practice of dentistry. Overall mean appreciation for the experience ranged from 14.50 to 15.14 on the 20‐point scale. These findings about students' and mentors' positive perceptions of the experience suggest that mentor groups may be a potentially valuable strategy to promote dental students' reflection.